Concrete bridge strengthening and repair - Kennedy Reid, Iain L. (Thomas Telford, 2009)
Covering a wide range of structural elements and related defects, this collection of twenty concrete bridge strengthening and repair case studies showcases solutions to real problems encountered in the field and the processes by which those solutions were developed.